Peripheral nervous system involvement in systemic lupus erythematosus: a retrospective study on prevalence, associated factors and outcome. (April 2019) - Bortoluzzi, A; Piga, M; Silvagni, E; Chessa, E; Mathieu, A; Govoni, M
Background: Despite its potentially significant impact on disease outcome, peripheral nervous system involvement in systemic lupus erythematosus has received little attention. Objective: The objective of this study was to assess the prevalence and clinical features of peripheral nervous system involvement in a large cohort of systemic lupus erythematosus patients. Methods: The records of systemic lupus erythematosus patients examined at two tertiary referral centres over a period of 14 years (from 2000 to 2014) were analyzed. Peripheral nervous system events were ascertained according to the 1999 American College of Rheumatology case definitions and by using an attribution algorithm for neuropsychiatric events. Prevalence of peripheral nervous system in systemic lupus erythematosus and demographic, clinical and laboratory features were assessed. Patients with peripheral nervous system events were compared with a control group of systemic lupus erythematosus patients without peripheral nervous system involvement. Results: In a retrospective cohort of 1224 patients, the overall prevalence of peripheral nervous system involvement was 6.9% (85 patients, 95% confidence interval 0.06–0.08), with 68% of peripheral nervous system events attributable to systemic lupus erythematosus. Polyneuropathy was the most common manifestation observed (38 events, 39.2%), followed by cranial neuropathy in 30 cases (30.9%) and 12 cases of single (12.4%) or multiple (eight events, 8.2%) mononeuritis. The average age of systemic lupus erythematosus onset was significantly higher in patients with peripheral nervous system events than in controls (mean ± standard deviation: 45.9 ± 14.8 vs. 37.1 ± 14.0) and they were more likely to have higher SLEDAI-2K and SLICC/ACR Damage Index scores, as well as hypertension and livedo reticularis. A subgroup analysis of events deemed to be systemic lupus erythematosus-related provided similar results. Conclusion: Peripheral nervous system manifestations are a potential complication of systemic lupus erythematosus. Careful neurological assessment should therefore be included in the diagnostic workup of patients with systemic lupus erythematosus, especially in those with later onset and greater damage and disease activity.